Lo sviluppo di Digidactic tools nella didattica museale tradizionale ed interattiva: casi studio di collezioni archeologiche toscane - Bombardieri, Luca; Jasink, Anna Margherita (Archeomatica, 2014)
The increasing research interest in creating new dedicated Digital tools for Didactic purposes can be opportunely labelled ‘Digidactic', as a new definition for a wide and complex research field. Such a trend revealed interesting applications to Humanities and, in particular, to the wide horizon of studies of the Ancient World. Digital and interactive tools have been recently improved in building up Virtual Galleries for Archaeological Museum Collections, but have been also positively applied to the Epigraphic, Paleographic and Philological Research. With the aim to outline an overall picture of this dynamic area of interest, this paper describes the recent initiatives and main research lines promoted by the @egean lab in Florence in the field of the Aegean and Cypriote Bronze Age. An overall picture of the main on-going researches on this topic is also presented as an Appendix dedicated to the DigiDactic activities in Tuscany.